Implementasi Metode SAW dan SMART dalam Pemilihan Jam Tangan Terbaik - Segar Napitupulu; Aulia Rizky Muhammad Hendrik Noor Asegaff; Mirza Ilhami; Ali Akbar Lubis; Wenripin Chandra (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2024)
Nowadays watches have become important items that are effective in telling time and complementing your appearance. Along with the rapid development of information technology, watches with various brands, specifications and prices have emerged. As a result, people become confused in choosing due to various considerations, so a calculation method that produces a ranking assessment to help in choosing a watch is needed. Therefore, research was carried out using the SAW and SMART methods, both of which are included in the Multiple Criteria Decision Making (MCDM) which can calculate various alternatives and attributes. Based on the research results, it was found that the SAW and SMART methods showed similar top rankings with the suitability level of the SAW method with 99.53033% and the SMART method with 99.42684%.